2014
DOI: 10.1093/humrep/deu137
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive choices and outcomes after freezing oocytes for medical reasons: a follow-up study

Abstract: This study was not externally funded. There are no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…If assisted reproductive treatments involving IVF are needed thereafter, the ovaries are often difficult to access for ovum pickup. Ovarian stimulation in connection with subsequent cryopreservation of oocytes or embryos before cancer treatment is thus indicated in such cases [ 6 , 30 34 ]. However, even if ovarian function is preserved, or oocytes or embryos have been cryopreserved, irradiation of the uterus may cause irreversible damage.…”
Section: Introductionmentioning
confidence: 99%
“…If assisted reproductive treatments involving IVF are needed thereafter, the ovaries are often difficult to access for ovum pickup. Ovarian stimulation in connection with subsequent cryopreservation of oocytes or embryos before cancer treatment is thus indicated in such cases [ 6 , 30 34 ]. However, even if ovarian function is preserved, or oocytes or embryos have been cryopreserved, irradiation of the uterus may cause irreversible damage.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the provision of accurate information on which to base realistic expectations, particularly for fertility preservation in women, is limited because the practice is still in its infancy and long-term outcome data are scarce [9, 52]. The limited existing evidence suggests that the rate of utilization of stored material among women who freeze oocytes or embryos before cancer treatment is low and that most post-treatment pregnancies occur spontaneously or as a result of ART with fresh oocytes [53, 54]. A recent review of 30 studies reporting reproductive outcomes for men who had stored sperm before undergoing cancer treatment found that only 8% had returned to use their stored sperm.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study in 2014 included a cohort of 85 women who cryopreserved their oocytes between 2009 and 2012 [11]. A total of 68 women, followed up for an average 25.3 months, returned the questionnaire (response rate: 80 %).…”
Section: Discussionmentioning
confidence: 99%
“…Three out of the eight pregnancies had resulted in live births, two resulted in miscarriages and three were ongoing. Most women (71 %) intended to conceive with their cryopreserved oocytes as a last resource option [11]. After a mean follow-up of 2 years, none of the women with a medical reason to cryopreserved oocytes had used her oocytes.…”
Section: Discussionmentioning
confidence: 99%